Examining Tourist Satisfaction with Tourism Infrastructure in West Bandung District, West Java, Indonesia - Syam, Rachmat (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Regardless of how attractive the attractions offered by a tourist destination, the lack of public facilities, accommodation, and the quality of infrastructure can be an obstacle to the success of tourism development, especially when it is related to its role in providing satisfaction to tourists. This also happened in West Bandung District, as one of the tourist destinations in West Java Province. Therefore, it is necessary to study how influential the quality of tourism infrastructure is on tourist satisfaction and its implications for tourism development in West Bandung District. Using descriptive research methods and through a quantitative approach from 160 tourists as respondents, it was found that the tourist satisfaction variable proved to be significantly affected by the tourism infrastructure variable, with a coefficient of determination of 0.65 (65%). Meanwhile, three dimensions of tourism infrastructure used (transportation, environment, and social), the transportation dimension is considered to have the most conditions that need to be improved because it only achieves a percentage of 64.7% of the achievement of the ideal score, followed by the social dimension (74%) and the environmental dimension. (76%). Although in general the actual condition of tourism infrastructure variables in West Bandung District is quite good, improvement is needed, especially in the transportation dimension in order to maximize the performance of the tourism industry, as recommendation and suggestions for local government and further research.